Community-Based Urban Farming in Yogyakarta: Building Social Capital and Resilience for Sustainable Empowerment Family - Rafika Perdana, Fahmi (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
This study attracted researchers to examine empowerment efforts based on Adult Farmer Groups by involving family members and using social capital owned by members of the Gemah Ripah Adult Farmer Group (AFG) in Bausasran Village Yogyakarta City. The study used a qualitative research method with purposive sampling as a sampling technique for determining informants. Data collection was carried out through observation, in-depth interviews, and documentation to be analyzed. Resulting that empowerment in AFG is sought and has brought various benefits for empowerment and family socio-economic resilience. Social capital is used in this empowerment effort, emphasizing family functions, namely the socialization function and the economic function. In the existing efforts and empowerment, there is potential for its sustainability, namely various forms of social capital that are still maintained and refreshed in the dynamics of AFG. There is support from residents, government, universities, the private sector, and the media. Meanwhile, the obstacles faced are that there are still some residents or family members who do not yet have awareness or concern about the essence of urban agriculture, including the young people who are more challenging to empower than the elderly, then the busyness constraint which is a classic obstacle for urban society.